Dampak Pemberdayaan Karyawan Terhadap Upaya Pemulihan Kualitas Layanan - Kawiana, I Gede Putu; Komang Candra Dewi, Luh; Yudy Wijaya, Putu (Institut Teknologi dan Sains Mandala, 2024)
The Covid-19 pandemic has provided many lessons for front-line employees for their responsiveness in efforts to restore service quality. Predictions from the service recovery model were tested on employees and consumers with variable empowerment on the training and autonomy components as predictor models. Empowerment through training and autonomy leads to higher satisfaction with aspects of employees' jobs. Finally, consumer satisfaction is created after the service is created by higher employee responsiveness.